2019
DOI: 10.1126/science.aav5386
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel dysfunction in human neuronal models of Angelman syndrome

Abstract: Disruptions in the ubiquitin protein ligase E3A (UBE3A) gene cause Angelman syndrome (AS). Whereas AS model mice have associated synaptic dysfunction and altered plasticity with abnormal behavior, whether similar or other mechanisms contribute to network hyperactivity and epilepsy susceptibility in AS patients remains unclear. Using human neurons and brain organoids, we demonstrate that UBE3A suppresses neuronal hyperexcitability via ubiquitin-mediated degradation of calcium- and voltage-dependent big potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 48 publications
6
118
0
Order By: Relevance
“…Two kinds of genetic modeling have been performed using cells either from individuals whose genetic contributions are unknown or undefined, so called idiopathic [59,60,[112][113][114][115][116][117][118][119][120], or from individuals harboring major effect mutations that are presumed causal or which have been engineered to carry these mutations. These mutations include ASD-associated CNVs such as 15q11q13 deletion (Angelman syndrome) [121] and duplication (Dup15q syndrome) [122], 22q11.2 deletion (DiGeorge syndrome) [123,124], 16p11.2 deletion and duplication [125], and 15q13.3 deletion [126], as well as single-gene mutations including SHANK3 [127][128][129][130], CHD8 [131,132], NRXN1 [133][134][135][136][137], NLGN4 [138], EHMT1 (Kleefstra syndrome) [139], PTCHD1-AS [140], UBE3A (Angelman's syndrome) [141], and CACNA1C (Timothy syndrome) [142] (summarized in Table 1). In this review, we will not discuss fragile X syndrome, Rett's syndrome, and tuberous sclerosis-related autism as they have all been extensively reviewed previously [148][149][150][151][152][153][154].…”
Section: Main Findings From Stem Cell Models Of Asd To Datementioning
confidence: 99%
“…Two kinds of genetic modeling have been performed using cells either from individuals whose genetic contributions are unknown or undefined, so called idiopathic [59,60,[112][113][114][115][116][117][118][119][120], or from individuals harboring major effect mutations that are presumed causal or which have been engineered to carry these mutations. These mutations include ASD-associated CNVs such as 15q11q13 deletion (Angelman syndrome) [121] and duplication (Dup15q syndrome) [122], 22q11.2 deletion (DiGeorge syndrome) [123,124], 16p11.2 deletion and duplication [125], and 15q13.3 deletion [126], as well as single-gene mutations including SHANK3 [127][128][129][130], CHD8 [131,132], NRXN1 [133][134][135][136][137], NLGN4 [138], EHMT1 (Kleefstra syndrome) [139], PTCHD1-AS [140], UBE3A (Angelman's syndrome) [141], and CACNA1C (Timothy syndrome) [142] (summarized in Table 1). In this review, we will not discuss fragile X syndrome, Rett's syndrome, and tuberous sclerosis-related autism as they have all been extensively reviewed previously [148][149][150][151][152][153][154].…”
Section: Main Findings From Stem Cell Models Of Asd To Datementioning
confidence: 99%
“…Moreover, loss-of-function mutations in E6AP associate with Angelman syndrome [38][39][40] and elevated gene dosage with autism spectrum disorders 41 . How aberrant E6AP mechanistically contributes to these neurological diseases is an active area of investigation; however, E6AP was recently found to ubiquitinate calcium-and voltagedependent potassium channels, the dysfunction and hyperexcitability of which is associated with Angelman syndrome 42 . E6AP distributes in an isoform-dependent manner between the nucleus and cytosol of neurons 43,44 and contains an N-terminal Zn-binding AZUL (amino-terminal zinc-binding domain of ubiquitin E3a ligase) domain 45 that binds to Rpn10 in the proteasome 46 , and is required for E6AP nuclear localization 44 .…”
mentioning
confidence: 99%
“…These results are in line with previous studies from our laboratory and others 11,12 that revealed hyperexcitability in cultured FXS neurons induced by overexpression of Neurogenin-2 compared to isogenic control. Interestingly, neurons develop to form hyperexcitable networks in other intellectual disability and autism spectrum disorders, such as Kleefstra syndrome, Angelman syndrome and idiopathic ASD [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%